PENGEMBANGAN E-CATALOGUE SEBAGAI MEDIA PROMOSI PADA PLATFORM INSTAGRAM BANK PEREKONOMIAN RAKYAT DELTA ARTHA KENCANA KABUPATEN MALANG - Ahmad Fauzi; Heru Utomo; Firmansyah, Ananda Rizki (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The growth of social media has encouraged companies to utilize it as a digital promotion tool. BPR Delta Artha Kencana faced challenges in efficiently presenting its product catalog through Instagram. This study aims to develop an e-catalogue as a promotional medium on Instagram and to measure its design effectiveness using the EPIC model. This research used action research as its method. Data collection techniques included interviews, observations, documentation, and questionnaires, with data processed using Likert scales, simple tabulation, and EPIC rate analysis covering the dimensions of Empathy, Persuasion, Impact, and Communication. The results showed that the e-catalogue design, developed and linked through Linktree in the Instagram bio, helped the audience easily access financial service information from BPR Delta Artha Kencana. Effectiveness assessment using the EPIC model achieved an average score above 4 across all dimensions, indicating that the design was considered effective. This study concludes that using an e-catalogue through the Instagram platform is an effective promotional strategy for BPR Delta Artha Kencana.